The DACAPO-PESO campaign: Dynamics, Aerosol, Cloud and Precipitation Observations in the Pristine Environment of the Southern Ocean: An overview - Vogl, T.; Schimmel, W.; Seifert, P.; Kalesse-Los, H.; Radenz, M.; Ansmann, A.; Baars, H.; Barja, B.; Bühl, J.; Engelmann, R.; Floutsi, A.; Foth, A.; et al. (Universität Leipzig, 2022)
This article gives an overview of the DACAPO-PESO field experiment, which has taken place in Punta Arenas, Chile, from November 2018 to November 2021, and showcases first exciting research results that have already emerged from it. In diesem Artikel wird ein Überblick über das DACAPO-PESO Experiment gegeben, welches von November 2018 bis November 2021 in Punta Arenas, Chile, stattgefunden hat. Außerdem werden erste spannende Forschungsergebnisse vorgestellt, die bereits daraus gewonnen wurden.